Application of Anterior Segment Optical Coherence Tomography in Pediatric Ophthalmology - Ricardo Salles Cauduro; Caroline do Amaral Ferraz; Maira Saad Ávila Morales; Patricia Novita Garcia; Yara Cristina Lopes; Paulo Henrique Souza; Norma Allemann (Journal of Ophthalmology)
Purpose. Application of anterior segment optical coherence (AS-OCT) in pediatric ophthalmology. Methods. Retrospective clinical study case series of 26 eyes of 19 pediatric patients throughout a 21-month period, presenting anterior segment pathologies, were submitted to AS-OCT examination (OCT Visante, 1310 nm, Zeiss), noncontact technique, no sedation requirement. Results. AS-OCT images were obtained from 19 patients (range: 2 months to 12 years). Clinical diagnosis of anterior segment abnormalities included cornea disease (n=7), congenital anterior segment conditions (n=10), ocular trauma (n=1), anterior segment surgeries (n=2), iridocorneal angle abnormalities (n=4), intermediate uveitis (n=2). The most common OCT findings were corneal hyperreflectivity and thickening (n=15), shallow anterior chamber with iris-lens diaphragm anterior displacement (n=4), atypical corneal curvature (n=4), corneal thinning (n=4), peripheral synechiae with angle closure (n=3), increased anterior chamber depth (n=2), and proximal portion of glaucoma drainage tube (n=2). Conclusion. In the present study, noncontact AS-OCT demonstrated to be a feasible technique to evaluate the anterior segment providing anatomic details and useful to clarify diagnosis in the pediatric population.